2016
DOI: 10.3390/ijerph13050513
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Behaviors in Swimming Pool Users: Influence of Knowledge of Regulations and Awareness of Health Risks

Abstract: Background: Swimming pool attendance exposes users to infection and chemical risks that could be largely reduced with the adoption of healthy behaviors. This study aims to investigate if the knowledge of swimming pool regulations and awareness of health risks can be associated with users’ health-related behaviors. Methods: A cross-sectional study was conducted using self-administered questionnaires to collect data from two different target groups of swimming users: 184 adults and 184 children/adolescents. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
3
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
2
26
3
4
Order By: Relevance
“…Although approximately 83% of children and 80% of adults stated they were aware of the rules, only 2% of people could correctly identify why the rules were in place. Additionally, results suggest that there is no correlation between viewing regulations and adopting the healthy behaviour, although an adoption of healthy behaviour (or decrease in unhealthy behaviour) was observed to increase with awareness and education level (Gallè et al, 2016). These studies show that more attention to swimmer education is required in order to decrease swimmer input to pools, which would minimise DBP formation and generally increase the quality of the swimming pool environment.…”
Section: Swimmers: Activity and Usagementioning
confidence: 76%
“…Although approximately 83% of children and 80% of adults stated they were aware of the rules, only 2% of people could correctly identify why the rules were in place. Additionally, results suggest that there is no correlation between viewing regulations and adopting the healthy behaviour, although an adoption of healthy behaviour (or decrease in unhealthy behaviour) was observed to increase with awareness and education level (Gallè et al, 2016). These studies show that more attention to swimmer education is required in order to decrease swimmer input to pools, which would minimise DBP formation and generally increase the quality of the swimming pool environment.…”
Section: Swimmers: Activity and Usagementioning
confidence: 76%
“…The most common educational level among the parents was university degree. 7 In our study 31.5% and 22.5% of the participants attend swimming pool 1 hour and >6 hours per week respectively. Among the males (130), 40% of participants were learner or beginner, 16% of participants attend swimming pool for exercise.…”
Section: Resultsmentioning
confidence: 46%
“…From previous literature, 80% of the participants follow swimming pool regulations, sample size was calculated. 7 Considering 5% alpha error, 95% confidence interval and 80% power of the test, using following formula sample size found to be 171 and rounded to 200.…”
Section: Methodsmentioning
confidence: 99%
“…So far, hygiene-related behaviour in swimming pools has not been widely discussed. In the last decade, several studies, mostly from Italy, investigated hygiene-related behaviour of pool users by conducting surveys among swimmers in order to collect data (Amodio et al, 2014;Bonini et al, 2011;Gallè et al, 2016;Liguori et al, 2007;Pasquarella et al, 2013;Pasquarella et al, 2014;Wiant, 2012). These studies revealed that some pool users were urinating while bathing, not showering before entering the pool, not wearing footwear, and not using a footbath and were even swimming when having skin wounds, infectious skin diseases and diarrhoea.…”
Section: Hygiene-related Behaviourmentioning
confidence: 99%